Electoral contention and violence (ECAV): A new dataset. (September 2019) - Daxecker, Ursula; Amicarelli, Elio; Jung, Alexander
Recent elections in Afghanistan, Bangladesh, Côte d'Ivoire, Egypt, Iraq, Kenya, Nigeria, and Pakistan have displayed substantial contestation and violence. A growing literature explores the causes and consequences of electoral contention and violence, but researchers lack comprehensive, disaggregated data establishing a substantive link between elections and violence. The Electoral Contention and Violence (ECAV) dataset conceptualizes electoral contention as nonviolent or violent events of contestation by state or non-state actors related to national elections. The data contain more than 18, 000 events of election-related contention covering 136 countries holding competitive national elections between 1990 and 2012. This article describes the scope of ECAV, presents the project's definition of electoral contention and the variables included, and outlines the coding procedure. We then compare ECAV to other datasets on electoral contention. Cross-national and subnational analyses of electoral competition and violence show that the data are useful for assessing the global and subnational implications of existing theories. ECAV addresses current data limitations by focusing on election-related contention, by using clear criteria to determine whether events are election-related, and by identifying the timing, geocoded location, and actors involved.